Experimental study on constitutive relation of the high performance marine structural steel under extreme cyclic loads. (15th November 2018) - Ma, Houbiao; Yang, Yang; He, Zheng; Jia, Ziyue; Zhang, Yahui
Abstract: Jacket offshore platform serving in the marine environment is often subjected to severe dynamic loads such as winds, waves, currents and earthquakes. The alternating stress state of jacket offshore platform will lead to the degradation of mechanical properties of the structural steel, which results in the decline of the overall bearing capacity. In this paper, eighteen types of cyclic loading program designed according to the characteristics of the steel and extreme cyclic loads are presented for the first time. The hysteresis behavior of structural steel NV-D36 under various cyclic loading program is studied. The changing process of energy dissipation capacity of the steel under different loading program is compared. The hysteresis skeleton curve of steel under variable amplitude cyclic loading is fitted based on the basis of the classical Ramberg-Osgood model. The parameters of combined hardening of the steel based on Chaboche constitutive model are calibrated. The results of the cyclic loading are numerically simulated with the obtained hysteresis skeleton curves and parameters. The combined hardening criterion can be used to analyze the responses of the steel under cyclic loading, and the parameters can be applied to study the dynamic properties of the jacket offshore platform of structural steel NV-D36. Highlights: In this paper, the hysteresis behaviors of structural steel NV-D36 for jacket offshore platform under various cyclic loading programs are studied. The changing process of energy dissipation capacity of the steel under different loading programs is compared. The hysteresis skeleton curve of steel under variable amplitude cyclic loading is fitted based on the basis of the classical Ramberg-Osgood model. The parameters of combined hardening of the steel NV-D36 based on Chaboche constitutive model are calibrated. The parameters can be applied to study the dynamic properties of the jacket offshore platform of structural steel NV-D36.